Expression level, correlation, and diagnostic value of serum miR-99a in pulmonary fibrosis in patients with acute respiratory distress syndrome - Lanlan Chen; Qihong Zhuang (Journal of Cardiothoracic Surgery)
Abstract Background Acute respiratory distress syndrome (ARDS) is a prevalent critical condition encountered in clinical settings and is characterized by high mortality. This research investigated miR-99a in diagnosing ARDS and its role in predicting pulmonary fibrosis (PF) among ARDS patients, to identify novel and effective biomarkers for ARDS. Materials and methods In this study, 128 patients with ARDS were selected as the experimental group, and 98 healthy people were included as the control group. ELISA measured the expression levels of IL-6, TNF-α, and IL-8, and the expression of miR-99a was measured by qRT-PCR. ROC curve evaluated the diagnostic value of miR-99a in ARDS patients and PF. Logistic regression evaluated the independent risk factors for PF in ARDS patients. Results This research demonstrated that miR-99a and inflammatory factors (IL-6, TNF-α, and IL-8) were markedly elevated in ARDS patients. The expression levels of miR-99a exhibited a significant correlation with the Murray score, PaO2/FiO2 ratio, APACHE II score, and occurrence of PF in ARDS patients. Furthermore, miR-99a displayed a robust distinguishing capacity for ARDS patients. Notably, miR-99a was found to be highly expressed within the PF subgroup of ARDS patients. It was recognized as a critical risk factor for PF occurrence in ARDS individuals and demonstrated considerable predictive potential. Conclusion The miR-99a could potentially be a promising biomarker for ARDS and predict the risk of PF in ARDS patients.